Purpose and technological properties of granular media for vibration finishing and grinding processing - Mitsyk, Аndrii; Fedorovich, Vladimir; Ostroverkh, Yevgeniy (Національний технічний університет "Харківський політехнічний інститут", 2023)
The purpose and characteristics of granular working media used in vibration processing operations are given. It is indicated that the purpose of granular media is their contact interaction with the processed part surface under conditions of various energy parameters. This interaction is accompanied by elastic-plastic deformation, micro-cutting, adhesion and mechanic-chemical processes. Indicators of technological and operational properties for various types of granular media are given, including the intensity of material removal from the processed surface, cutting ability, wear resistance and achieved surface roughness. The physical and technological parameters of granular media have been established, including deformability, hardness during finishing and hardening operations and surface roughness of the media granules. The influence of the parameters of processing media granules on the productivity of vibration treatment has been determined. It is shown that such parameters are the binding of the granules material, its wear resistance, grain material, granulation and the shape of individual granules. It is noted that the choice of granule sizes depends on two main factors such as: the necessity to obtain a given roughness and high productivity of vibration operations. It was revealed that to ensure high surface cleanliness, the use of small granules of the medium is required, but to obtain high productivity, the use of large granules is required. Approximate dependencies have been determined that relate the size and weight of granules of the processing medium and the processed parts. It is indicated that the best results in achieving high quality of the processed surface and sufficient productivity are provided by granular media with a shape close to a sphere. It is noted that granules in the form of cones, pyramids, prisms and other forms are used for the successful processing of hard-to-reach places in the form of small holes, straight and sharp angles in the interface of the surface of parts, niches or pockets. Such granules are specially manufactured from a mixture of grinding powders of various grain sizes and an inorganic binder based on clays. The features of the physical and technological parameters of processing media are given.

Наведено призначення та характеристика гранульованих робочих середовищ, що використовуються на операціях віброобробки. Вказано, що призначення гранульованих середовищ полягає в їхній контактній взаємодії з оброблюваною поверхнею деталі в умовах різних енергетичних параметрів. Така взаємодія супроводжується пружнопластичною деформацією, мікрорізанням, адгезійними та механохімічними процесами. Наведено показники технологічних та експлуатаційних властивостей для різних видів гранульованих середовищ, серед яких інтенсивність зйому матеріалу з оброблюваної поверхні, різальні здібності, зносостійкість, досягнута шорсткість поверхні. Встановлено фізико-технологічні параметри гранульованих середовищ, у тому числі деформаційну здатність, твердість при виконанні оздоблювально- зміцнювальних операцій, шорсткість поверхні гранул середовища. Визначено вплив параметрів гранул обробних середовищ на продуктивність вібраційної обробки. Показано, що такими параметрами є зв’язка матеріалу гранул, його зносостійкість, матеріал зерна, грануляція та форма окремих гранул. Зазначено, що вибір розмірів гранул залежить від двох основних факторів: необхідності отримання заданої шорсткості та високої продуктивності вібраційних операцій. Виявлено, що для забезпечення високої чистоти поверхні потрібно застосування гранул середовища малих розмірів, а для отримання високої продуктивності застосування гранул великої грануляції. Встановлено орієнтовні залежності, що зв’язують розміри та вагу гранул обробного середовища та оброблюваних деталей. Вказано, що найкращі результати досягнення високої якості обробленої поверхні та достатньої продуктивності дають гранульовані середовища за формою близькі до сфери. Зазначається, що для успішної обробки важкодоступних місць у вигляді дрібних отворів, прямих та гострих кутів у поєднанні поверхні деталей, ніш, кишень використовуються спеціально виготовлені із суміші шліфувальних порошків різної зернистості та неорганічної зв’язки на основі глин, гранули у вигляді конусів, пірамід, призм та інших форм. Надано особливості фізико-технологічних параметрів обробних середовищ.
Призначення та технологічні властивості гранульованих середовищ для оздоблювально-зачищувальної вібраційної обробки
Keywords: vibration treatment; granular medium; processed parts, physical and technological parameters; productivity of vibration processing; віброобробка; гранульоване середовище; фізико-технологічні параметри; продуктивність віброобробки